Teachers’ Competency in Content Knowledge and Pedagogy in Buhi South District, Philippines - Manigbas, Jimmy III; Ollet, Aljon L.; Noble, Mary Paulyn L.; Angeles, Jean R.; Cayetano, Nerissa M.; Fucio, Modesto P. (PT. BATARI EDU CALYA, 2024)
This study investigated the competency of teachers in content knowledge and pedagogy. This involved the forty-five Elementary teachers teaching Grade levels 1 to 3 in the nine selected public elementary schools in the Department of Education (DepEd), Division of Camarines Sur, Buhi South District, Philippines, for the School Year 2022-2023. The study results revealed that teachers are Highly competent in content knowledge and pedagogy except in the utilization and application of research-based knowledge and principles of teaching and learning. The results further revealed that their professional peers were the most influential factor that affects them. Quantitative data shows that teachers' competency along content knowledge application within and across the curriculum areas, as well as the utilization of Mother tongue, Filipino, and English language, were significant in their demographic characteristics. It recommends that DepEd officials prioritize teachers' professional development that is tailored to their needs to continuously improve